PERILAKU BURUNG MURAI BATU (Copsychus malabaricus) SIAP PRODUKSI - Agung Dwi Saputro; Khaira Nova; Tintin Kurtini (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2016)
behaviour) white rumped shama which ready for production. This research was held on March 2016 in Mr Wahidin’s white rumped shama captivity, Seputih Mataram, Bandar Jaya, Central Lampung. The object being observed are 10 pairs of white rumped shama that are ready for production. The behaviour’s data of white rumped shama taked by behaviour observation and recorded using a video camera. The Data analyzed descriptively by explaining everything that happened in the research location of the behaviour of white rumped shama that are ready for production. The results showed the average percentage of white rumped shama’s behaviour includes of eating, drinking, and cleaning up of beak in females higher than males. The average percentage of white rumped shama’s behaviour includes of perching, resting, approached, and basking in males higher than females. White rumped shama behaviour cans indicate the readiness of white rumped shama’s production. Keywords: White Rumped Shama, White Rumped Shama Behaviour, Production Readiness.